The Effect of Filler Content on the Tensile Behavior of Polypropylene/Cotton Fiber and poly(vinyl chloride)/Cotton Fiber Composites - Elsadig Mahdi (Materials, 2020)
This paper investigates the effect of filler content on the mechanical properties of cotton fiber (CF) on the CF/PP and CF/PVC composites under quasi-static loading. For this purpose, experimental tensile tests were carried out on dog-bone specimens, cut out from hot and cold press molded square plates of different fiber weight contents. The results obtained show that the filler content appears to have a strong influence on mechanical energy absorption, and failure characteristics. It was also found that the stiffness for both sets of material increases with the addition of filler. On the other hand, the ductility for both sets of the material increases with the addition of filler. The microscopic morphology study indicates that CF/PP possesses a glossy surface appearance compared to CF/PVC, which possesses a porous surface. Micro-scale damage characteristics from tensile tests indicate that material experienced shear failure, matrix cracking, fiber breakage, fiber fracture, and fiber pullout. The phenomenon of matrix crazing experienced by CF/PP composites was also observed.